Selective Requirement for Maintenance of Synaptic Contacts onto Motoneurons by Target-Derived trkB Receptors - Xiya Zhu; Patricia J. Ward; Arthur W. English (Neural Plasticity)
Synaptic contacts onto motoneurons were studied in mice in which the gene for the trkB neurotrophin receptor was knocked out selectively in a subset of spinal motoneurons. The extent of contacts by structures immunoreactive for either of two different vesicular glutamate transporters (VGLUT1 and VGLUT2), the vesicular GABA transporter, or glutamic acid decarboxylase 67 (GAD67) with the somata of motoneurons, was studied in wild type and trkB knockout cells in tamoxifen treated male and female SLICK-trkB−/− mice. Selective knockout of the trkB gene resulted in a marked reduction in contacts made by VGLUT2- and GAD67-immunoreactive structures in both sexes and a significant reduction in contacts containing only glycine in male mice. No reduction was found for glycinergic contacts in female mice or for VGLUT1 immunoreactive contacts in either sex. Signaling through postsynaptic trkB receptors is considered to be an essential part of a cellular mechanism for maintaining the contacts of some, but not all, synaptic contacts onto motoneurons.